Pulse Width and Stability Dependence of Passively Q-Switched Erbium-Doped Fiber Laser on MWCNTs’ SA Concentration - Dunya Zeki Mohammed; Abd Al- Hadi Al-Janabi (Journal of Madenat Alelem University College, 2020)
The concentration effect of multi-walled carbon nanotubes (MWCNTs) dispersed in polyvinyl alcohol (PVA) polymer matrix has experimentally investigated as a saturable absorber (SA) to stabilize the Q-switching performance of ring cavity erbium-doped fiber laser (EDFL). The output pulse width was reduced from 4.6 to 4.4 down to 4 µs corresponding to an increase in MWCNTs’ SA concentration from 0.25 to 0.5 up to 0.75 wt%. The Q-switched EDFL output was very stable as the MWCNTs’ concentration increased from 0.5 to 0.75 wt%, while the lowest MWCNTs concentration 0.25% showed a noticeable instability.